The Contribution of Entrepreneurial Orientation to the Performance of Small and Medium Enterprises in Bandar Lampung Culinary Sector - Feti Arman (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
The objective of this research is to evaluate the partial and simultaneous influence of entrepreneurial orientation variables, which include dimensions of innovativeness, risk-taking, and proactiveness, on the performance of micro, small, and medium enterprises (MSMEs) in the culinary sector. The population of this study comprises culinary MSMEs in Way Halim, Bandar Lampung, specifically those around PKOR Bandar Lampung. The reason for sampling in this location is due to the high number of culinary MSMEs and the rapid development of culinary activities in the area. The sampling technique used is purposive sampling, with the sample criterion being culinary MSMEs that have been in operation for at least one year. Based on hypothesis testing using multiple regression, it is found that entrepreneurial orientation variables, including innovativeness, risk-taking, and proactiveness, significantly influence MSME performance both simultaneously and partially.